Circadian conformational change of the Neurospora clock protein FREQUENCY triggered by clustered hyperphosphorylation of a basic domain - Querfurth, Christina; Diernfellner, Axel; Gin, Elan; Malzahn, Erik; Höfer, Thomas; Brunner, Michael (Molecular cell, 2011)
In the course of a day, the Neurospora clock protein FREQUENCY (FRQ) is progressively phosphorylated at up to 113 sites and eventually degraded. Phosphorylation and degradation are crucial for circadian time keeping, but it is not known how phosphorylation of a large number of sites correlates with circadian degradation of FRQ. We show that two amphipathic motifs in FRQ interact over a long distance, bringing the positively charged N-terminal portion in spatial proximity to the negatively charged middle and C-terminal portion of FRQ. The interaction is essential for the recruitment of casein kinase 1a (CK1a) into a stable complex with FRQ. FRQ-bound CK1a progressively phosphorylates the positively charged N-terminal domain of FRQ at up to 46 nonconsensus sites, triggering a conformational change, presumably by electrostatic repulsion, that commits the protein for degradation via the PEST1 signal in the negatively charged central portion of FRQ.